Employee assistance programme in health care: a framework for best practice and quality management - Kruger, Willem Hendrik (University of the Free State, 2011)
Employee assistance was initiated early in the 19th century in the United States of America to assist employees with alcohol abuse in the workplace. During the 1970s, the concept of an employee assistance programme (EAP) was adapted to assist employees not only with alcohol-related problems, but also with personal and other work-related problems resulting in poor work performance. It is evident from the literature that no EAP is the same and that researchers have developed the seven EAP core technologies to promote uniformity within the field of employee assistance. The aim of this study was to establish a framework for a best-practice EAP for the health care sector and the quality management thereof. As background to the study, the researcher conducted an extensive literature review to investigate the current situation on the utilisation of EAPs in various industries worldwide. The literature review was used as a guide during the empirical phase of the study in order to gain more in-depth knowledge with regard to employee assistance in the health care sector. A case study design as a qualitative research approach was applied. Five focus group discussions were held with supervisors from various levels in several health care institutions as a data-gathering method. Several criteria for the bestpractice EAP were identified during the data gathering and a six-round Delphi survey was conducted to achieve consensus with regard to the criteria to be included in the best-practice EAP. Accordingly, a framework for a best-practice EAP and the quality management thereof was developed. The management of health care institutions should realise that their health care workers are their most valuable resource and that there is a need to assist them with personal and work-related problems. The framework was developed specifically for a health care institution with the option to adapt it in order to suit the unique requirements of each individual health care institution. This proposed framework could be used to develop an institution-unique EAP. The establishment of a workplaceunique EAP will show employees that they are regarded as the most valuable resource in the health care institution. The overall goal and objectives, as set out for the research study, were addressed and realised, and meaningful recommendations in the field of employee assistance have been made. The framework for a best-practice EAP is in line with the core technologies of EAPs, the needs of supervisors in health care institutions and the EAPs used internationally. The proposed framework includes the following main aspects, namely the need for an EAP in a health care institution, the strategic approach for the development of such a programme, the structure and processes of an EAP, and the evaluation of an EAP in terms of its effectiveness. The framework will contribute significantly to the management of human resources in the health care industry and provide a supportive work environment for health care workers to ensure healthy and productive employees.
Thesis (Ph.D. (Community Health))-University of the Free State
Keywords: Employee assistance programs -- Health and safety; Health promotion; Health services administration; Delphi survey; Focus group discussion; Case study design; Qualitative research; Quality management; Best-practice; Behavioural health care; Employee performance; Employee assistance programme